Dynamical analysis of turbulent liquid phase in two-phase pipe flow - Munir, S. (Science Society of Thailand under Royal Patronage, 2014)
An experimental study was conducted to evaluate dynamic structures embedded in a liquid and turbulent characteristics of slug flow in a horizontal pipe. Initially, single liquid phase flow was considered at a flow rate of 120 l/m and later on slug flow was generated by the introduction of a gas phase at the rate of 40 l/m keeping the liquid phase flow at the same rate. Particle image velocimetry was employed to calculate the two-dimensional instantaneous velocity field of the liquid phase. The turbulent velocity fields and dynamics of the liquid phase flow were investigated by proper orthogonal decomposition analysis. The structures containing the most energy were successfully revealed. The energy distributions of the spatial and temporal modes were also obtained. Â© 2014, Science Society of Thailand under Royal Patronage. All rights reserved.